OC-068 The Impact Of Endoscopic Therapy On Patient-perceived Outcome And Quality Of Life In Sphincter Of Oddi Dysfunction. (9th June 2014) - Paranandi, B; Cheung, VTF; Joshi, D; El-Sayed, GH; Johnson, GJ; Pereira, SP; Webster, GJ; Chapman, MH
Abstract : Introduction: Biliary Sphincter of Oddi dysfunction (SOD) is a benign but often debilitating condition. Significant improvement in pain following endoscopic sphincterotomy or sphincteroplasty (ES) in patients with Type 1 SOD, is excellent. Symptomatic improvement in patients with type 2 or 3 SOD is less favourable (reported 50–70% and 30–50% respectively). We aim to determine the impact of ES, on pain symptoms and global quality of life (QOL) in these groups, which has not previously been well defined. Methods: An ERCP database and electronic clinic lists (from September 2011 to 2013) were analysed to identify all cases of suspected SOD. Patients underwent a telephone questionnaire. The Glasgow Benefit Inventory (GBI), which assesses multiple physical, emotional and social parameters, was used to quantify global post-interventional QOL benefit. Total GBI scores can range from -100 (maximal negative benefit) to +100 (maximal positive benefit). Results: 163 new patients with suspected biliary SOD were identified of whom 89 underwent ERCP. 3 patients were excluded due to an alternative diagnosis at ERCP. The remaining cohort was predominantly Female (87%) and White British (86%) with median age 37 years (range 18–69). 88% had undergone prior cholecystectomy. Patients were attributed with the following pre-test diagnoses – 20/86 (23%) SOD1, 53/86 (62%) SOD2, 13/86 (15%) SOD3. Median post-ERCP follow up was 12 months (range 2–27). In patients who underwent endotherapy and completed questionnaires: 93% (14/15) SOD1, 76% (36/48) SOD2 and 83% (10/12) SOD3 subjectively reported pain improvement post-ERCP (within median 1 month). Sustained response (median 6 months) was noted in 60, 30 and 46% of SOD 1/2/3 respectively. Median total GBI scores in the patients who had sustained improvement were +44 (SOD1), +31 (SOD2) and +29 (SOD3). There was a clear correlation between subjective response to ES and GBI scores (see table). Negative total scores were recorded across all SOD subtypes in patients who had no symptom improvement whatsoever following ES. Total GBI scores in all categories were higher in SOD1 than SOD2 than SOD3. Conclusion: ES for SOD1 appears to provide sustained benefit in symptoms and QOL above that achieved in SOD2/3. QOL measured by GBI is strongly correlated to symptomatic response to ES despite pain response being only a minor contributor to the GBI rating. Therefore, GBI may be helpful to determine clinical, emotional and social factors that could help to predict those patients who will respond to ES. Disclosure of Interest: None Declared.